The time is ripe: a scoping review of risk factors and barriers in preconception care - Puspitasari, Halfie Zaqiyah Gusti; Widyawati; Hapsari, Elsi Dwi; Nuzulullail, Agung Subakti; Irawan, Dana Prayoga (BKM Public Health and Community Medicine, 2025)
Purpose: Preconception care (PCC) is fundamental to preparing for a healthy pregnancy by reducing risk factors. However, there are still various obstacles to its implementation. This review aims to identify risk factors and barriers to accessing and implementing PCC. Methods: The research design used a scoping review compiled from articles obtained from four databases: PubMed, ScienceDirect, ProQuest, and Web of Science. The inclusion criteria include original articles published between 2020 and 2025 that are fully accessible, written in English, and reports on PCC risk factors and barriers. Exclusion criteria include theoretical articles without practical applications, research related to specific medical conditions, and articles that are not relevant to the research objectives. The selection process was conducted in accordance with the PRISMA-ScR (2020) guidelines. Data from selected articles were extracted and synthesized narratively in accordance with the Update Methodological Guidance for the Conduct of Scoping Reviews (2020). Results: A total of 896 articles were found in the search. After screening, 14 articles were selected for analysis. These articles represented eight countries, including Ethiopia, the United States of America, and Australia. Low PCC knowledge, poor obstetric history, and maternal age were the most frequently discussed risk factors for PCC. Meanwhile, barriers to PCC implementation were attributed to the lack of PCC guidelines and service standards, low PCC education and promotion, and low motivation and knowledge of healthcare workers. Conclusion: The implementation of PCC remains hindered by policy limitations, system readiness, and health worker capacity, underscoring the need for further research as a basis for developing comprehensive guidelines.